Prevailing I292V PB2 mutation in avian influenza H9N2 virus increases viral polymerase function and attenuates IFN-β induction in human cells. (15th July 2019) - Gao, Weihua; Zu, Zhipeng; Liu, Jiyu; Song, Jingwei; Wang, Xinyu; Wang, Chenxi; Liu, Litao; Tong, Qi; Wang, Mingyang; Sun, Honglei; Sun, Yipeng; Liu, Jinhua; et al.
Abstract : Adaptation of PB2 protein is important for the establishment of avian influenza viruses in mammalian hosts. Here, we identify I292V as the prevalent mutation in PB2 of circulating avian H9N2 and pandemic H1N1 viruses. The same dominant PB2 mutation is also found in most human isolates of emergent avian H7N9 and H10N8 viruses. In human cells, PB2-292V in H9N2 virus has the combined ability of conferring higher viral polymerase activity and stronger attenuation of IFN-β induction than that of its predecessor PB2-292I. IFN-β attenuation is accompanied by higher binding affinity of PB2-292V for host mitochondrial antiviral signalling protein, an important intermediary protein in the induction of IFN-β. In the mouse in vivo model, PB2-292V mutation increases H9N2 virus replication with ensuing increase in disease severity. Collectively, PB2-292V is a new mammalian adaptive marker that promotes H9N2 virus replication in mammalian hosts with the potential to improve transmission from birds to humans.